Introducing Phenomenology in Action for Researching Networked Learning Experiences - Dohn, Nina Bonderup; Adams, Cathy; Healey-Benson, Felicity; Johnson, Mike (Proceedings of the International Conference on Networked Learning, 2024)
This Round Table aims to introduce and discuss the book Phenomenology in Action for Researching Networked Learning, forthcoming (2024) in the Springer Book Series Research in Networked Learning. The wider aim of the Round Table is to continue our explorations of the place of phenomenology in networked learning. After a brief introductory overview of the book, our four invited discussants will present their response to the book, thus initiating general discussion with the audience on the roles, possibilities and challenges of using phenomenology to investigate networked learning.